DINAMIKA PANCASILA PADA ERA GLOBALISASI - Zulkarnain Zulkarnain (KEADILAN PROGRESIF, 2019)
The position of Pancasila as a staatsfundamentalnorm and Pancasila as an ideology is verymandatory to be instilled and implied specifically to the State elite from both the political andeconomic aspects of the nation and state. The problem is whether Pancasila is able toovercome the problems of the nation at this time. The method used is the Normative andEmpirical Juridical approach. Data is sourced from library studies and field studies. Dataanalysis was carried out qualitatively. The results of the study show that Pancasila as a stateideology is still very capable of overcoming the problems of the nation today, including aproblem that is tentative with the political elite in its existence for the welfare of the nationand state both in terms of politics, development and the economy. To construct it is verynecessary to do methods that include: 1) Development of state politics to maintain theintegrity and sustainability of the nation, 2) Developing the content of Pancasila in thenational education system and 3) Establishment of a special body for the formulation andcivilization of Pancasila